PELAKSANAAN KOORDINASI DALAM MEWUJUDKAN GREEN CITY - M. Fajar Anugerah; Sujianto Sujianto; Adlin Adlin (Universitas Riau, 2016)
Implementation Coordination in Making Geen City. Initiative green city embodies hasstrategic significance because it was motivated by several factors, including the rapid growth ofcities and the implications for the emergence of a variety of urban problems such as traffic congestion,floods, slums, social inequality and reduced area of green open space. There are four attributesto realize the green city of Green Planning and Design, Green Open Space, Green Waste, GreenTransportation. The method used in this study is a qualitative research method. Based on theresults of this research is that the functions of planning and organizing the management functionsof local government in the implementation of coordination in realizing green city of Pekanbarusignificantly affect its implementation. This is because in the planning function realizing greenplanning and design in planning the environmental documents for the initiators or businessowners they are still viewed as a burden (in terms of both budget and implementation), not as anobligation to manage the environment and poor law enforcement effort/activities that do notprepare and implement environmental documents. In the monitored object embodies a green openspace is still focused on vital objects without seeing other objects as objects to monitor road thatfocus on the way the protocol/parent and offices that focus on office close to the center ofgovernment. organizing coordination function Environment Agency is still lacking coordinationin the delivery of test equipment to realize the integrated transport emissions or green transportation.